Management of a Suspected Case of Gallbladder Cancer with Individualised Homoeopathy: A Case Report - Singh, Lalith; M., Kanagavali; Rija, Maga; Manoharan, Raja (Homœopathic Links, 2021)
Background India has a highest incidence of gallbladder cancer (GBC) and contributes 10% of global GBC burden. The risk of GBC increases with age. The first peak of GBC occurs at 50 to 60 years and second peak at 70 to 80 years. In this article, the authors have presented a suspected case of GBC in a male patient of 65 years. Radiological reports also show presence of gallstones in this case. Studies show that four out of five persons with GBC have gallstones when they are diagnosed. The patient had pain in right upper abdomen, weight loss for few months, liver function test was highly altered and a space-occupying lesion was found in the gallbladder on radiological investigation. Patient was receiving treatment in a private medical college and hospital where computed tomography (CT) scan and magnetic resonance cholangiopancreatography detected gallbladder mass . Age of the patient, significant weight loss, presence of gallstones, abnormal liver function test and gallbladder mass have raised a suspicion of gallbladder cancer. Patient was advised for CT-guided biopsy by doctors of private hospital, but patient did not go for biopsy because of his belief that biopsy may worsen malignancy. Patient came to National Institute Homoeopathy for homoeopathic treatment to avoid biopsy and surgery.Method After proper case taking and repertorisation, a constitutional medicine Carcinosin was prescribed in Q-potency. Patient was kept under follow-up for more than a year and the patient is still under treatment. During treatment different potency of Carcinosin was prescribed in ascending scale.Results During the course of treatment, significant clinical, radiological and biochemical and pathological improvement has occurred.Conclusion Homoeopathy is among the commonly used alternative approaches in cancer. It is being widely used as palliative and curative care in patients suffering from cancer. Though studies on the use of homoeopathy in cancer after surgery, radiotherapy and chemotherapy have been reported, clinical trials on effects of homoeopathy in cancer are rare. In this case report, a suspected case of GBC was treated by higher homoeopathic dilution with significant improvement.
Keywords: gallbladder cancer; individualised homoeopathy; Carcinosin; constitutional medicine